Development of Functional Golden Milk by Incorporating Curcuma amada and Stevia by Response Surface Methodology: Functional Golden Milk by Incorporating Curcuma amada and Stevia - Sanya Sharma, Pallawi Joshi, Shubhendra Singh; Anil Kumar Chauhan (Indian Journal of Dairy Science, 2023)
The objective of this study was to develop and optimize golden milk using the incorporation of Curcuma amadaand stevia into the milk and preserve it using pasteurization. The analysis was carried out by incorporating Curcuma amada powder and stevia in the milk and optimizing using the Response surface methodology. A set of thirteen experiments were done in whichoptimized golden milk with the maximum desirability was produced using 3.43 percent Curcuma amada and 0.35 percent stevia, according to the outcomes of the variable optimization.The physicochemical and biochemical characteristics of the milk were also accessed. The antioxidant activity of Functional golden milk is 56.14and total phenolic content was found to be38.04 to 36.95 mg GAE. The product was accessed for its shelf life using a sensory score and found that it was stable for 7 days @ 4◦C